Thyroid function, renal events and mortality in chronic kidney disease patients: the German Chronic Kidney Disease study - Schultheiss, Ulla T.; Steinbrenner, Inga; Nauck, Matthias; Schneider, Markus; Kotsis, Fruzsina; Baid-Agrawal, Seema; Schaeffner, Elke; Eckardt, Kai-Uwe; Koettgen, Anna; Sekula, Peggy (Clinical Kidney Journal, 2021)
Background. Hypothyroidism and low free triiodothyronine (FT3) syndrome [low FT3 levels with normal thyroid-stimulating hormone (TSH)] have been associated with reduced kidney function cross-sectionally in chronic kidney disease (CKD) patients with severely reduced estimated glomerular filtration rate (eGFR) or end-stage kidney disease (ESKD). Results on the prospective effects of impaired thyroid function on renal events and mortality for patients with severely reduced eGFR or from population-based cohorts are conflicting. Here we evaluated the association between thyroid and kidney function with eGFR (cross-sectionally) as well as renal events and mortality (prospectively) in a large, prospective cohort of CKD patients with mild to moderately reduced kidney function.
CRIS-Team WoS Importer:2021-05-28